Development of an automated on-chip bead-based ELISA platform. Issue 19 (7th October 2015) - Campbell, Jennifer; Pollock, Nira R.; Sharon, Andre; Sauer-Budge, Alexis F.
<x xml:space="preserve">Abstract</x> We present a lab-on-a-chip and associated instrument for heterogeneous enzyme-linked immunosorbent assay (ELISA)-based detection of proteins from liquid samples.